Innovation in Feed Technology for Self Sufficiency in Poultry Production - Tangendjaja, Budi (Indonesian Animal Sciences Society, 2007)
Indonesia is self sufficient in poultry production to meet the local demand for broiler and egg, mainly derived from modern poultry rather than the local village chicken. Feed may contribute up to 70% of total cost of poultry production. Poultry feed is formulated using least cost feed formulation technique to meet the bird requirement and composed by several ingredients both locally available and imported materials. Feed ingredients are classified based on energy sources, protein sources, agro-industrial by products, mineral sources and supplements. In many cases the poultry feed was supplemented with additives (antibiotics, enzymes, preservatives, etc.) to improve animal performance. In 2005, Indonesian feed production reached almost 7 million tonnes and comprised around 85% as poultry feed, while the rest for aquaculture, swine and others. Poultry feed is based on corn-soy diet and average corn usage may reach more than 55% while soybean meal more than 23%. Ingredients requirement has been calculated based on the feed production and in order to fulfill the requirement. In 2006, Indonesia will import more than 1.6 million tonnes of corn from Argentina, USA and China, and more than 1.5 million tonnes of protein meal due to insufficiency of the local production. Major problems related in feed production are raw materials supply, quality and price fluctuation along with limited information. Several research have been conducted to use unconventional ingredients as protein sources such as local beans, leguminous seeds, leaf protein, animal by products Â but they were limited in availability. Research to improve protein level from carbohydrate source or by products had been attempted but it was not feasible for commercial feed industry. In future, technology innovation should be developed based on the existing problems related with feed industry including the areas to improve production efficiency, managing feed quality, processing technology and feed additives development. Scenario of poultry production for 2020 has been exercised and discussed in this paper. Â Key words: Poultry, feed, technology, innovation, feed ingredient